Legal Review of Action Criminal Exploitation of Street Children at Crossroads in the Name of Beggars - Anwar, Hairul Kifly; Ramadhan, Muhammad Fauzi; Cindrapole, Andi Cakra (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the government's prevention and control efforts against criminal acts of exploitation of street children at intersections on behalf of beggars and applicable legal regulations related to criminal acts of exploitation of street children at intersections on behalf of beggars. Empirical legal research method. The results of this study indicate that, ) Knowing and analyzing the applicable legal effort regulations related to the criminal act of exploitation of street children at intersections on behalf of beggars. In accordance with the results of the author's research, the government's prevention and control efforts against criminal acts of exploitation of street children at intersections on behalf of beggars, Knowing and analyzing the government's prevention and control efforts against criminal acts of exploitation of street children at intersections on behalf of beggars. Suggestions from the author for the future, Concrete steps are needed to strengthen local regulations governing the exploitation of street children in Parepare City. The local government needs to immediately establish a specific local regulation to protect street children. In addition, it is important to provide adequate shelter facilities for street children after being disciplined, and improve coordination between institutions such as SATPOL-PP, PKSAI, and social rehabilitation centers to provide more effective reintegration and rehabilitation services.